Minimization of DC-Link Capacitance in Voltage Source Rectifiers through Nonlinear Controls Based on Lyapunov's Direct Method - Vygoder, Mark; Cuzner, Robert M.; Armstrong, Brian S. R. (2023 IEEE International Conference on Electrical Systems for Aircraft, Railway, Ship Propulsion and Road Vehicles & International Transportation Electrification Conference (ESARS-ITEC), 2023)
The increased switching frequency offered by Silicon Carbide (SiC) based Multi-chip Power Modules may allow designers to reduce the size and weight of passive elements while still meeting converter specifications. For the 3-phase Voltage Source Rectifier (VSR), as switching frequency increases, the DC-link capacitor may be reduce while maintaining the same voltage ripple. However, an often overlooked part in sizing the DC-link capacitance is the converter's stability. The use of conventional control methods, such PI-based controls, may lead to larger DC-link capacitance to prevent instability, minimizing the value proposition of Wide Band Gap-based power conversion. Applications like electrified shipboard or more electrical aircraft can be extremely sensitive to increases in size/weight due to limited space and/or significant annualized fuel costs. To this end, this paper explores, through simulation, a nonlinear control method based on Lyapunov's direct method published 25 years ago to minimize DC-link capacitance of an SiC-based VSR.